Development Of Learning And Classroom Management Competencies Of Student Teachers Using The Transformative Learning Concept - et. al., Suttipong Boonphadung, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The development of competency in learning and classroom management of student teachers according to the transformative learning concept is an important student-centered teaching method in correspondence with the development of students to become teachers in the New Normal era. The objectives of this research were to assess and compare students’ competency levels in learning and classroom management with 86% competency criteria and to assess the level of their transformative learning. The sample of the research was 32 third year student teachers of the Faculty of Education in Suan Sunandha Rajabhat University. The research was conducted in the academic year 2020. The sample was selected through cluster random sampling. The research instruments included 15 transformative learning-based lesson plans, a knowledge test on learning and classroom management, an assessment form on the learning and classroom management, and an assessment form on transformative learning. The data was analyzed using Mean, standard deviation, and t-test. The research results revealed that the competency level of student teachers was at a high level or 80.46%, however their competencies were still significantly lower than the 86% competency criteria with the statistical significance at the .01 level. The findings also showed that the levels of the student teachers ‘transformative learning was high (Mean=4.35, S.D.=1.02). The research results are beneficial for the academic affairs such as publication of teaching materials developed in accordance with the educational guidelines for transformative learning to the Graduate Teacher Production Unit. The results reveal an insight into the management of teacher education in the Faculty of Education and related agencies for enhancing the quality of 21st century teacher. Moreover, the findings of this study also indicate the importance of teacher professional development programs and trainings that can encourage teachers to implement transformative learning methods in classrooms in order to develop their learners effectively and appropriately.